Pendampingan Pengelolaan Keuangan Berbasis Akuntansi Bagi Pelaku Umkm Di Kelurahan Renteng Kecamatan Praya Kabupaten Lombok Tengah - Murapi, Ikang; Ayu Oki Astarini, Dewa; Ketut Sriwinarti, Ni; Putri Fitri Ajiani, Ika; Muliani, Muliani; Bayu Bimantoro, Muh. (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
This community service activity aims to provide an understanding of the importance of financial reports for MSME actors in Renteng Village. Provide training and assistance so that partners are able to compile financial reports based on applicable accounting standards, implement them in their daily business. Based on initial communication with partners, information was obtained about the problems encountered, namely not understanding the importance and benefits of financial statements, not compiling financial reports that match accounting rules correctly, so that business developments are difficult to detect profits and losses. The solution offered is to provide training and assistance in the preparation of accounting-based financial reports. The implementation method used: lectures to convey the concept of the material, the practice of completing an accounting cycle in the form of cases, and providing assistance in the field. The results of monitoring and evaluation showed that the participants were able to absorb more than 55% of the training material provided. The participants also felt satisfied and saw that this training was important and useful. The results of the assistance in the field showed that most of the partners already had the understanding to prepare financial reports based on accounting principles with the guidance of the dedication team of the accounting study program lecturer at Bumigora University